2017
DOI: 10.1111/bjh.15051
|View full text |Cite|
|
Sign up to set email alerts
|

R‐CHOP versus dose‐adjusted R‐EPOCH in frontline management of primary mediastinal B‐cell lymphoma: a multi‐centre analysis

Abstract: Primary mediastinal (thymic) large B-cell lymphoma (PMBCL) is an uncommon subtype of non-Hodgkin lymphoma (NHL) that presents with a mediastinal mass and has unique clinicopathological features. Historically, patients with PMBCL were treated with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy ± involved field radiation. Since a phase II trial, published in April 2013, demonstrated excellent results using dose-adjusted (DA) R-EPOCH (rituximab, etoposide, prednisone, vinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 28 publications
8
75
1
Order By: Relevance
“…An ongoing randomized prospective clinical trial (NCT01599559) will help to answer this question and reduce the frequency of empiric radiation after R‐CHOP chemotherapy. At present, most centres continue to use consolidate radiation after R‐CHOP in PMBCL, as we have shown in our study (Shah et al , ).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…An ongoing randomized prospective clinical trial (NCT01599559) will help to answer this question and reduce the frequency of empiric radiation after R‐CHOP chemotherapy. At present, most centres continue to use consolidate radiation after R‐CHOP in PMBCL, as we have shown in our study (Shah et al , ).…”
supporting
confidence: 66%
“…We recently published our results from a multi‐center analysis evaluating two common frontline treatment regimens for patients with Primary Mediastinal B cell Lymphoma (PMBCL), DA‐R‐EPOCH (dose‐adjusted rituximab, etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin) and R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone). In our non‐randomized, retrospective analysis we found that while progression‐free survival (PFS) favoured DA‐R‐EPOCH (although not statistically significant), overall survival (OS) was similar at 2 years, 89% for R‐CHOP vs. 91% for DA‐R‐EPOCH (Shah et al , ). As a result, we were hesitant to make a strong recommendation for one specific regimen for the frontline management of PMBCL.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…It is characterized by PD-1 overexpression, constitutional JAK-STAT activation, and subtype-specific GEP [77]. Historically treated with RCHOP and consolidative RT, PMBCL has now shown excellent outcomes after DA-EPOCH-R chemotherapy alone, obviating the need for RT in the predominantly young, female population affected by this disease [7880]. The low risk of CNS recurrence does not warrant prophylaxis.…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%
“…We read with interest the report by Shah et al () on a retrospective, multi‐centre analysis comparing R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) to DA‐EPOCH‐R (dose‐adjusted rituximab, etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin) as front‐line therapy for patients with primary mediastinal B‐cell lymphoma (PMBCL). The authors report that DA‐EPOCH‐R produced significantly greater complete remissions (CR) compared to R‐CHOP but similar 2‐year overall survivals, of 89% and 91%, respectively, suggesting equivalence.…”
mentioning
confidence: 99%